Relationship between longitudinal changes in amyloid deposition and incident dementia in non‐demented individuals age 80+. (20th December 2022) - Lopez, Oscar L.; Villemagne, Victor L; Cohen, Ann D; Snitz, Beth E; Aizenstein, Howard J; Klunk, William E; Mathis, Chester; Chang, YueFang; Kuller, Lewis H
Abstract: Background: Incident dementia increases with age and is associated with amyloid deposition. There is little knowledge about the progression of amyloid deposition in non‐demented individuals age 80+. The purpose of this study was to determine the relationship between changes in amyloid deposition over time and incident dementia in non‐demented individuals followed for a period of 11 years. Methods: We examined a group of elderly participants (baseline age: 85.86 + 2.84) who had clinical evaluations from 2009 to 2020 and up to 5 measurements of Pittsburgh compound‐B (PiB)‐PET. 94 participants had two PiB‐PET scans, 76 three, 18 four, and 10 five. Mean age was 95 at 2020, at which time 49% of the participants with two or more scans developed dementia and 61% were deceased. Results: There was a gradual increase in amyloid deposition in all participants whether they were considered amyloid positive or negative at baseline. Time to dementia in baseline amyloid negative participants was 7.09 + 2.90 years (range 2.92 – 11.22), and in amyloid positive participants 5.6 + 2.10 (range 2.27 – 9.67). Baseline amyloid deposition was a significant predictor of increase deposition over time. In a Cox model controlled for age, sex, education level, APOE‐4 allele, mortality, and baseline MMSE, change in amyloid deposition from 2009 to 2010‐11 was not significantly associated with incident dementia (HR 2.19 (0.41‐11.73). Baseline continuous measures of amyloid deposition, cortical thickness and white matter lesions (WMLs) were strong predictors of dementia. Approximately 70% of the participants who converted to dementia had either significant amyloid deposition (SUVR ≥1.67), cortical thickness, or WMLs positivity at baseline. Conclusions: There was a substantial and steady amyloid deposition in this age group. There were very few (10%) participants who developed dementia without being amyloid positive. Individuals classified as amyloid negative at baseline became incident amyloid positive (SUVR > 1.67) prior to the dementia diagnosis, and most individuals who were amyloid positive at baseline developed dementia, especially when neurodegeneration was present.